2013
DOI: 10.2478/hukin-2013-0045
|View full text |Cite
|
Sign up to set email alerts
|

Are Various Forms of Locomotion-Speed Diverse or Unique Performance Quality?

Abstract: The forward-sprint is considered to be, and is regularly performed as, a unique measure of “on-ground” linear-speed performance. Thus far, no investigation has simultaneously studied different forms of linear-speed or investigated whether different forms of linear-speed should be observed as unique performance quality. The purpose of this study was to determine (I) the achievements (i.e. execution time), and (II) the reliability and inter-relationships between various linear-speed performances. The participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Throughout this test, the testing scenario was simple (1,2), and the subjects knew it in advance. As for the SNG-RAT, the timing began the moment each subject crossed the IR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout this test, the testing scenario was simple (1,2), and the subjects knew it in advance. As for the SNG-RAT, the timing began the moment each subject crossed the IR.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of this significant correlation, however, it is evident that reactive and nonreactive agilities shared ,50% of the common variance, which indicates that these 2 capacities should be observed as independent qualities (1,16,18). While studying rugby-specific agility, Australian authors identified an even smaller percentage of common variance between reactive and nonreactive components (12).…”
Section: Stop'n'go Reactive-agility Testmentioning
confidence: 97%
“…Knowing this relationship allows for a more precise exercise prescription and a better understanding of relationships related to muscular balance of the lower body. While there are references to backwards walking [1113], running [14,15], forward and backward arm cycling [16], forward and reverse wheelchair ergometry [17] and forward pedaling [18,19], backwards pedaling research is limited in scope, mainly focusing upon understanding submaximal clinical applications [37,20]. To the author’s knowledge, the relationship in maximal power output between a reverse pedaling WAT to the forward pedaling WAT has not been investigated.…”
Section: Introductionmentioning
confidence: 99%